Proceedings of IEEE 14th International Semiconductor Laser Conference
DOI: 10.1109/islc.1994.519309
|View full text |Cite
|
Sign up to set email alerts
|

Gain-dependent polarization properties of vertical-cavity lasers

Abstract: Abstract-We show that the partitioning of power into the two orthogonal eigen polarizations of infra-red gain-guided verticalcavity lasers depends upon the relative spectral overlap of the nondegenerate polarization cavity resonances with the laser gain spectrum. Furthermore, at the condition where the polarization resonances and the peak laser gain are aligned, abrupt switching of power between the eigen polarizations is observed as the gain sweeps through the polarization resonances. The gain-dependence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 5 publications
0
43
0
Order By: Relevance
“…Polarization properties of VCSELs are extremely interesting and yet, poorly understood. It is well known [1] that VCSELs generally exhibit abrupt polarization switching as a function of bias current, from higher to lower frequency mode (type-I switching) or vice-versa (type-II switching), depending on the detuning between the polarization modes and their relative position with respect to the gain spectrum [2]. It has also been found that the VCSEL polarization can be affected by the temperature [2], magnitude and directionality of current injection [3][4][5][6], stress [7] and with polarized optical injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polarization properties of VCSELs are extremely interesting and yet, poorly understood. It is well known [1] that VCSELs generally exhibit abrupt polarization switching as a function of bias current, from higher to lower frequency mode (type-I switching) or vice-versa (type-II switching), depending on the detuning between the polarization modes and their relative position with respect to the gain spectrum [2]. It has also been found that the VCSEL polarization can be affected by the temperature [2], magnitude and directionality of current injection [3][4][5][6], stress [7] and with polarized optical injection.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known [1] that VCSELs generally exhibit abrupt polarization switching as a function of bias current, from higher to lower frequency mode (type-I switching) or vice-versa (type-II switching), depending on the detuning between the polarization modes and their relative position with respect to the gain spectrum [2]. It has also been found that the VCSEL polarization can be affected by the temperature [2], magnitude and directionality of current injection [3][4][5][6], stress [7] and with polarized optical injection. Theoretical modeling based on 'Spin-Flip Model' [8,9] has been successfully used to predict certain static [10,11] and dynamic [12][13][14] polarization properties of VCSELs.…”
Section: Introductionmentioning
confidence: 99%
“…Residual dichroism and birefringence, which are inevitably present, lead to different net gains of the polarization modes, thus slightly favoring one mode over the other at VCSEL threshold. Nevertheless, polarization switching and instabilities occur when changing VCSEL control parameters [5,6]. The most striking evidence is usually obtained in the Light output (L) vs. Pumping Current (I) curve (L/I curve),where, at a given current value, an abrupt switch occurs from one linear polarization (LP) state to the orthogonal one, often accompanied by a narrow hysteresis cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Emission in different polarization and transverse modes is usually found in solitary VCSELs. While the multitransverse mode emission is attributed to Spatial Hole Burning (SHB) effects [28][29][30], the polarization behavior of VCSELs can be influenced by a number of physical mechanisms [31][32][33][34]. Optical injection experiments have been usually performed using two different configurations.…”
Section: Introductionmentioning
confidence: 99%